Mandailing Customary Dowry Determination Practices in Padang Lawas District in Perspective of 'Urf Theory - M. Wildan Hamidi Pasaribu; Lempang Hasibuan; Abdulsalam Al Anesi (Faculty Sharia of State Islamic University (UIN) Palangka Raya, 2024)
Dowry is a mandatory gift by a man to a woman who wants to get married. this study aims to determine the practice of determining dowries in traditional marriages in Padang Lawas Regency, north Sumatra, the impact of dowry practices on marriage, and how the views of scholars and community leaders related to the practice of determining dowries carried out by mandailing customs in Padang Lawas Regency, north Sumatra and if reviewed from the perspective of 'urf. the type of research used is qualitative research with an empirical approach using primary data and secondary data. The results of this study indicate that the tradition of the practice of determining dowry in Padang Lawas regency is still firmly held and inherited by the community as one of the marriage processions that must be obeyed. then the impact of the practice of determining the tuor if it does not get an agreement between the two sides of the family, the marriage is delayed, the marriage is canceled or can elope. furthermore, the practice of determining the dowry in mandailing traditional marriage in Padang Lawas from the perspective of 'urf, cannot be generalized into the category of 'urf shahih or 'urf fasid, but must be reviewed from each process. When viewed from the perspective of 'urf, the tradition of tuor (dowry) practice in padang lawas generally falls into the category of 'urf shahih, because there is no shara' argument that is violated. However, there are provisions of the tuor tradition that are different from the provisions of Islamic law, namely the delivery of the dowry, the dowry of the wife who was divorced before dukhul, and the fine of the dowry.